Pengaruh Dana Pihak Ketiga (DPK), NPF dan NOM Terhadap Return On Assets (ROA) Bank Panin Dubai Syariah Periode 2018-2023 - 10010320024, Maisa Ulfa; Zaini Abdul Malik; Intan Manggala Wijayanti (Bandung Conference Series: Syariah Banking, 2025)
Abstract. Bank Panin Dubai Syariah has experienced significant fluctuations in its Return on Assets (ROA), even reaching negative values in several periods. This indicates an imbalance in asset management and operational efficiency. ROA is influenced by several factors, such as Third Party Funds (DPK), Non-performing Financing (NPF), and Net Operating Margin (NOM). However, previous research has shown inconsistent results. This study aims to analyze the effect of DPK, NPF, and NOM on ROA at Bank Panin Dubai Syariah. This research uses a quantitative method with secondary data in the form of quarterly financial reports from 2018 to 2023. The analysis was conducted using multiple linear regression with the help of EViews 12 software. The results show that, partially, DPK and NOM have a positive and significant effect on ROA, with significance values of 0.0306 and 0.0000 respectively (less than 0.05). Meanwhile, NPF has no significant effect on ROA, as indicated by a significance value of 0.0617 (greater than 0.05). Simultaneously, DPK, NPF, and NOM significantly influence ROA with an F-statistic value of 4.015393 (greater than the F-table value of 3.10) and a significance level of 0.0000. Abstrak. Bank Panin Dubai Syariah mengalami fluktuasi signifkan pada Return On Asset (ROA), bahkan mencapai angka negative pada beberapa periode, yang mencerminkan ketidakseimbangan dalam pengelolaan asset dan efisiensi operasional. ROA di pengaruhi bebebrapa faktor, seperti Dana Pihak Ketiga (DPK), Non-performing Financing (NPF), dan Net Operating Margin (NOM), namun hasil penelitiansebelumnya menunjukan perbedaan. Penelitian ini bertujuan untuk menganalisis pengaruh DPK, NPF, dan NOM terhadap ROA pada Bank Panin Dubai Syariah. metode yang digunakan adalah kuantitatif dengan data sekunder berupa laporan keungan triwulanan periode 2018- 2023. Analisis dilakukan mengunakan regresi liner berganda dengan bantuan software Eviews 12. Hasil Hasil penelitian menunjukkan bahwa secara parsial, DPK dan NOM berpengaruh positif dan signifikan terhadap ROA dengan signifikansi masing-masing 0.0306 dan 0.0000 (lebih kecil dari 0,05). Sementara itu, NPF tidak berpengaruh signifikan terhadap ROA karena nilai signifikansi sebesar 0.0617 (lebih besar dari 0,05). Secara simultan, ketiga variabel tersebut berpengaruh signifikan terhadap ROA dengan nilai F-hitung 4.015393 (lebih besar dari F-tabel 3.10) dan nilai signifikansi 0.0000.